First detection of Colpodella spp. in Rhipicephalus annulatus and molecular characterization of piroplasmids in southern Egypt - Soliman, Ahmed M.; Mahmoud, Hassan Y. A. H.; Amer, Moaz M.; Mohamed, Samah; Hifumi, Tatsuro; Tsukiyama-Kohara, Kyoko; Tanaka, Tetsuya (Frontiers in Veterinary Science, 2025)
Piroplasmosis is a tick-borne disease that can affect livestock, particularly cattle. Its causative pathogens are intracellular apicomplexan parasites belonging to the order Piroplasmida. We recently identified one such emergent pathogen (Colpodella spp.) in ticks infesting camel in Egypt. Accordingly, we aimed to ascertain the presence of hemoprotozoan parasites in ticks infesting cattle. We removed ticks from household cattle during veterinary examinations, and submitted them for morphological examination and PCR analyses for species identification. Ticks and hemoprotozoan species obtained from tick samples were also evaluated using BLAST analysis, followed by confirmatory phylogenetic analyses. The collected ticks were identified as belonging to three species: Hyalomma dromedarii, Hyalomma marginatum, and Rhipicephalus annulatus. Phylogenetic analysis based on the 16S rRNA gene revealed that these ticks were clustered with those of the relevant species previously documented in Egypt. Molecular analysis targeting the 18S rRNA gene revealed Colpodella spp., the second such report in Egypt and the first in R. annulatus ticks infesting cattle. The Colpodella minimum infection rate (MIR) was 2.3% (per sample of pooled ticks from a single bovine host). Furthermore, Babesia bovis, Theileria. annulata, and Theileria orientalis were detected with MIRs of 3.5%, 4.7%, and 0.39%, respectively. In the phylogenetic analysis, each detected pathogen clustered with its corresponding species. Specifically, the Colpodella spp. were grouped with Colpodella spp. previously detected in Rhipicephalus microplus, Rhipicephalus haemaphysaloides ticks, and humans in China (accession numbers MH208620, MH208621, and GQ411073), and H. dromedarii ticks infesting camel in southern Egypt (accession numbers LC775361 and LC775361). We confirmed the detection of B. bovis and T. annulata through PCR assays with specific primers targeting the spherical body protein-4 gene and the major merozoite surface antigen gene, respectively. The detection of Colpodella spp. in ticks infesting cattle highlights the need for ongoing surveillance of this parasites. Both cattle and camels may serve as sentinel species, emphasizing the importance of monitoring these livestock for emerging parasites.